ATP‐Responsive Aptamer‐Based Metal–Organic Framework Nanoparticles (NMOFs) for the Controlled Release of Loads and Drugs. (20th July 2017) - Chen, Wei‐Hai; Yu, Xu; Liao, Wei‐Ching; Sohn, Yang Sung; Cecconello, Alessandro; Kozell, Anna; Nechushtai, Rachel; Willner, Itamar
Abstract : Nanoparticles consisting of metal–organic frameworks (NMOFs) modified with nucleic acid binding strands are synthesized. The NMOFs are loaded with a fluorescent agent or with the anticancer drug doxorubicin, and the loaded NMOFs are capped by hybridization with a complementary nucleic acid that includes the ATP‐aptamer or the ATP‐AS1411 hybrid aptamer in caged configurations. The NMOFs are unlocked in the presence of ATP via the formation of ATP‐aptamer complexes, resulting in the release of the loads. As ATP is overexpressed in cancer cells, and since the AS1411 aptamer recognizes the nucleolin receptor sites on the cancer cell membrane, the doxorubicin‐loaded NMOFs provide functional carriers for targeting and treatment of cancer cells. Preliminary cell experiments reveal impressive selective permeation of the NMOFs into MDA‐MB‐231 breast cancer cells as compared to MCF‐10A normal epithelial breast cells. High cytotoxic efficacy and targeted drug release are observed with the ATP‐AS1411‐functionalized doxorubicin‐loaded NMOFs. Abstract : Stimuli‐responsive DNA‐functionalized metal–organic framework nanoparticles (NMOFs) : The synthesis of NMOFs loaded with doxorubicin and capped with stimuli‐responsive DNAs that respond to biomarkers characteristic to cancer cells is described. By locking the drug‐loaded NMOFs with a DNA strand consisting of the AS1411 aptamer and the ATP aptamer, targeted permeation of the NMOFs into cancer cells, the ATP‐driven unlocking of the NMOFs, and drug release are demonstrated.